2003
DOI: 10.1074/jbc.m207269200
|View full text |Cite
|
Sign up to set email alerts
|

Altered Sphingolipid Metabolism inN-(4-Hydroxyphenyl)- retinamide-resistant A2780 Human Ovarian Carcinoma Cells

Abstract: In the present work, we studied the effects of fenretinide (N-(4-hydroxyphenyl)retinamide (HPR)), a hydroxyphenyl derivative of all-trans-retinoic acid, on sphingolipid metabolism and expression in human ovarian carcinoma A2780 cells. A2780 cells, which are sensitive to a pharmacologically achievable HPR concentration, become 10-fold more resistant after exposure to increasing HPR concentrations. Our results showed that HPR was able to induce a dose-and time-dependent increase in cellular ceramide levels in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 62 publications
4
70
1
Order By: Relevance
“…5,[12][13][14] Other studies have reported that apoptosis in response to HPR primarily occurs by a receptor-independent mechanism, which is accompanied by generation of reactive oxygen species (ROS), 15,16 alteration of mitochondrial membrane potential, 17,18 a decrease in Bcl-2 expression, 19 or an increase in ceramide levels. [20][21][22] The proto-oncogene c-Fos encodes a nuclear DNA binding phosphoprotein that dimerizes with the gene product of c-Jun to form the transcription factor activating protein 1 (AP-1). AP-1 converts extracellular signals into changes in the expression of specific target genes, which harbor the AP-1 DNA binding site(s) in their promoter regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[12][13][14] Other studies have reported that apoptosis in response to HPR primarily occurs by a receptor-independent mechanism, which is accompanied by generation of reactive oxygen species (ROS), 15,16 alteration of mitochondrial membrane potential, 17,18 a decrease in Bcl-2 expression, 19 or an increase in ceramide levels. [20][21][22] The proto-oncogene c-Fos encodes a nuclear DNA binding phosphoprotein that dimerizes with the gene product of c-Jun to form the transcription factor activating protein 1 (AP-1). AP-1 converts extracellular signals into changes in the expression of specific target genes, which harbor the AP-1 DNA binding site(s) in their promoter regions.…”
Section: Introductionmentioning
confidence: 99%
“…29 We also reported that HPR was able to induce ceramide levels in sensitive but not in resistant cells. 22 Using A2780 and A2780/ HPR cells and a panel of other human ovarian cancer cell lines, we examined the effects of HPR treatment on c-Fos expression to determine the role of the proto-oncogene in HPR-induced apoptosis. Our findings indicated that c-Fos inducibility and HPR-induced apoptosis are closely associated.…”
Section: Introductionmentioning
confidence: 99%
“…In 4-HPR-resistant ovarian carcinoma cells, increased ganglioside levels were demonstrated after treatment with 4-HPR compared to 4-HPR sensitive cells [73]. These data suggest that 4-HPR might be able to enhance GD2-directed immunotherapy via an increased GD2 expression on 4-HPR-resistant NB cells mediated by an evasion mechanism from toxic ceramide accumulation.…”
Section: Fenretinide or N-(4-hydroxyphenyl) Retinamide (4-hpr) Is A Smentioning
confidence: 72%
“…4-HPR treatment is known to induce an increase of gangliosides on 4-HPR-resistant ovarian cancer [73] and SH-SY5Y cells [69]. We expanded this attempt to multi-drug or partially resistant NB cells and show that 4-HPR induced an increase of GD2 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation